Role of the Endogenous Cannabinoid System in Nicotine Addiction: Novel Insights - Gamaleddin, Islam Hany; Trigo, Jose M.; Gueye, Aliou B.; Zvonok, Alexander; Makriyannis, Alexandros; Goldberg, Steven R.; Le Foll, Bernard (Frontiers in Psychiatry, 2015)
Several lines of evidence have shown that the endogenous cannabinoids are implicated in several neuropsychiatric diseases. Notably, preclinical and human clinical studies have shown a pivotal role of the cannabinoid system in nicotine addiction. The CB1 receptor inverse agonist/antagonist rimonabant (also known as SR141716) was effective to decrease nicotine-taking and nicotine-seeking in rodents, as well as the elevation of dopamine induced by nicotine in brain reward area. Rimonabant has been shown to improve the ability of smokers to quit smoking in randomized clinical trials. However, rimonabant was removed from the market due to increased risk of psychiatric side-effects observed in humans. Recently, other components of the endogenous cannabinoid system have been explored. Here, we present the recent advances on the understanding of the role of the different components of the cannabinoid system on nicotine’s effects. Those recent findings suggest possible alternative ways of modulating the cannabinoid system that could have implication for nicotine dependence treatment.